1981
DOI: 10.1002/art.1780240303
|View full text |Cite
|
Sign up to set email alerts
|

“Milwaukee shoulder”—association of microspheroids containing hydroxyapatite crystals, active collagenase, and neutral protease with rotator cuff defects. i. clinical aspects

Abstract: Four women, aged 63 to 90 years old, presented with mildly painful shoulders of decreased mobility or stability. Radiographic evidence of a complete tear of the fibrous rotator cuff was present in 7 of 8 shoulder joints. Microspheroids containing hydroxyapatite crystals were seen by scanning electronmicroscopy in 12 of 13 synovial fluid samples. All synovial fluids showed activated collagenase and neutral protease activity. This constellation of findings represents a heretofore undescribed syndrome which we ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
8

Year Published

1981
1981
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 282 publications
(79 citation statements)
references
References 18 publications
(21 reference statements)
1
70
0
8
Order By: Relevance
“…Sections were collected on a copper grid, which is responsible for the additional peaks. strengthened by McCarty et al who observed destructive arthropathy of the shoulders associated with the presence of microspheroids containing hydroxyapatite crystals, active collagenase, and neutral protease in the synovial fluid (28). Moreover, these authors showed that the synovial lining cells could phagocytize hydroxyapatite crystals (29) and that apatite crystals stimulated the secretion of collagenase and neutral protease by synovial cells in culture (30).…”
Section: Discussionmentioning
confidence: 98%
“…Sections were collected on a copper grid, which is responsible for the additional peaks. strengthened by McCarty et al who observed destructive arthropathy of the shoulders associated with the presence of microspheroids containing hydroxyapatite crystals, active collagenase, and neutral protease in the synovial fluid (28). Moreover, these authors showed that the synovial lining cells could phagocytize hydroxyapatite crystals (29) and that apatite crystals stimulated the secretion of collagenase and neutral protease by synovial cells in culture (30).…”
Section: Discussionmentioning
confidence: 98%
“…As noted by Silcox and McCarty (4), the PPi concentrations in CPPD deposition are lower during attacks of pseudogout. The "miscellaneous" group ( Table 2) included 1 patient with Milwaukee shoulder syndrome (25) who had the second highest PPi concentration recorded in this study. A correlation between synovial PPi concentration and ATPPPH activity was observed ( P < 0.01; r = 0.71) for all 37 patients studied ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Patients were selected by the staff of the Medical College of Wisconsin rheumatology clinic and the consulting staff at the time of diagnostic or therapeutic arthrocentesis, whenever at least 5 ml of SF could be obtained. Joint fluid was obtained from 41 patients: 8 with definite or classic RA, 3 with crystal-proven gout, 4 with primary OA, 12 with chondrocalcinosk (CPPD deposition disease) and with chronic noninflammatory effusions, 2 with pseudogout, 2 with OA secondary to trauma, 3 with Milwaukee shoulder syndrome (18), I with basic calcium phosphate deposition (191, 2 with renal disease treated by hemodialysis, 1 with postseptic arthritis, 1 with systemic lupus erythematosus (SLE), and 2 with undifferentiated chronic arthritis. Thirty-one of the patients were included in a previous study (10).…”
Section: Methodsmentioning
confidence: 99%